2022
DOI: 10.1159/000525187
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound Scores Progress Differently in Extreme and Very Preterm Infants after Birth: A Multicentre Prospective Study

Abstract: <b><i>Introduction:</i></b> The lung ultrasound score (LUS) has been suggested to predict moderate-severe bronchopulmonary dysplasia (msBPD) in preterm infants. We aimed to assess LUS evolution after birth in preterm infants and the effect of gestational age. <b><i>Methods:</i></b> This multicentre prospective observational study was performed with newborns born before 33 weeks of gestation. We created two groups: group 1 (23–27 weeks) and group 2 (28–32 weeks). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In infants born at 28–32 weeks of gestation, LUSs performed well in predicting the development of msBPD, similar to that observed in the total sample. LUSs decreased rapidly during the first week of life and remained high and stable in infants with evolving msBPD, as previously reported [ 12 , 21 ]. Interestingly, the present study found that the predictive performance of the clinical five-factor model was superior to that of LUSs on D14.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In infants born at 28–32 weeks of gestation, LUSs performed well in predicting the development of msBPD, similar to that observed in the total sample. LUSs decreased rapidly during the first week of life and remained high and stable in infants with evolving msBPD, as previously reported [ 12 , 21 ]. Interestingly, the present study found that the predictive performance of the clinical five-factor model was superior to that of LUSs on D14.…”
Section: Discussionsupporting
confidence: 85%
“…Alonso-Ojembarrena et al [ 12 ] and Raimondi et al [ 21 ] reported different LUS patterns from birth until 6–14 weeks in infants born before 28 weeks. Persistently high LUSs in the first 4 weeks after birth for infants with GA < 28 weeks were described, regardless of their subsequent evolution to msBPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Extremely preterm infants and very low birth weight infants had persistently high LUS during the first few weeks of life regardless to duration of IMV or development of bronchopulmonary dysplasia. 41,42 High LUS can be explained by pulmonary insufficiency of prematurity. To further investigate, we performed a subgroup analysis to identify LUS diagnostic accuracy in extremely preterm and very low birth weight infants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data indicate that extremely preterm infants are at a higher risk of requiring IMV and experiencing extubation failure, potentially due to lung immaturity 5 . Extremely preterm infants and very low birth weight infants had persistently high LUS during the first few weeks of life regardless to duration of IMV or development of bronchopulmonary dysplasia 41,42 . High LUS can be explained by pulmonary insufficiency of prematurity.…”
Section: Discussionmentioning
confidence: 99%